Hybrid Electro‐optical Stimulation Improves Ischemic Brain Damage by Augmenting the Glymphatic System - Min Jae Kim; Jiman Youn; Hong Ju Lee; Seo‐Yeon Lee; Tae‐Gyu Kim; Young‐Jin Jung; Yong‐Il Shin; Byung Tae Choi; Joonsoo Jeong; Hwa Kyoung Shin (Advanced Science)
Abstract Ischemic brain injury not only results in significant neurological, motor, and cognitive impairment but also contributes to the accumulation of toxic solutes and proinflammatory cytokines in the infarction region, exacerbating ischemic brain damage. The glymphatic system, which is crucial for brain waste clearance and homeostasis, is impaired by ischemic injury, highlighting the importance of developing therapeutic strategies for poststroke complications. Herein, a novel hybrid electro‐optical stimulation device is proposed that integrates near‐infrared micro‐light‐emitting diode with transparent microneedles, enabling efficient noninvasive stimulation of the cortical area for ischemic stroke treatment. This study investigates whether this hybrid electro‐optical stimulation enhances the glymphatic system function and ameliorates ischemic brain injury in the middle cerebral artery occlusion and reperfusion (MCAO/R) mice model. The results demonstrate that hybrid stimulation improves the neurological, motor, and cognitive functions and reduces brain atrophy following MCAO/R. Moreover, hybrid stimulation restores impaired glymphatic system function by modulation of aquaporin‐4 (AQP4) polarization and alleviates the accumulation of proinflammatory cytokines such as IL‐1β. Notably, AQP4 inhibition partly reverses the improved functional outcomes of hybrid stimulation. The findings suggest that targeting glymphatic drainage using hybrid electro‐optical stimulation is a promising therapeutic approach for treating ischemic brain injury.